Notes on the Early History of the Society of Antiquaries of Scotland, and the House in the Cowgate in which the Society and its Library and Museum were originally accommodated (Proceedings of the Society of Antiquaries of Scotland, 1911)
In November 1780 a meeting was called at which the formation of the society was proposed, and from which we may date its existence. A royal charter was obtained in 1782, whereby the reigning monarch is declared to be the patron of the Society. The first meeting at the house was held in April 1781. A history of the house and its depiction on early maps is presented.